Pigs, Purity, and Patrilineality: The Multiparity of Swine and Its Problems for Biblical Ritual and Gender Construction - Ruane, Nicole J. (Journal of Biblical literature, 2015)
The biblical characterization of pigs as impure has been interpreted in a variety of ways. Most have focused on the anomalies of the pig compared with other domesticated animals, especially with regard to their alimentary processes. All interpretations, however, have neglected a primary feature of pigs that makes them radically different from all other clean land animals, namely, that they are multiparous, giving birth in litters. This article argues that the multiparity of pigs makes them incompatible with other ritually clean land animals in four ways: (1) All clean land animals are uniparous. (2) As multiparous animals, pigs do not bear a true firstborn male, which would make them different from all clean domesticated animals. This feature is most important because the sanctity of the domesticated firstling is recognized by all pentateuchal sources, and, furthermore, the ideology of the firstborn male is integrally related to the human practices of inheritance, lineage, and wealth management. (3) The multiparity of pigs highlights abundant female fertility in comparison with the more controlled and managed fertility seen in the biblical purity systems. (4) Multiparous animals are capable of bearing the offspring of multiple sires simultaneously, a phenomenon that conflicts with the biblical focus on paternity.